The Plasma Proteome and Risk of Future Venous Thromboembolism—Results from the HUNT Study - Brækkan, Sigrid K.; Onsaker, Asbjørn L.; Nøst, Therese H.; Tang, Weihong; Hindberg, Kristian D.; Morelli, Vania M.; Guan, Weihua; Jonasson, Christian; Folsom, Aaron R.; Hveem, Kristian; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2024)
This study aimed to identify novel plasma proteins associated with first-lifetime venous thromboembolism (VTE) and molecular pathways involved in VTE pathogenesis.A case–cohort comprising incident VTE cases (n = 294) and a randomly sampled age- and sex-weighted subcohort (n = 1,066) was derived from the Trøndelag Health Study (HUNT3, n = 50,800). Blood samples were collected and stored at cohort inclusion (2006–2008), and participants were followed up to 5 years. Proteome-wide analyses was performed using the 7k SomaScan® proteomics platform, and weighted Cox-regression models adjusted for age, sex, and sample batch were conducted, with the Bonferroni method applied to account for multiple testing. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were applied on the top-ranked 200 proteins associated with VTE.Out of 7,288 human proteins, 7 proteins were significantly associated with higher VTE risk with p-value <6.9 × 10−6 (hazard ratios per 1 standard deviation increase in protein levels ranging from 1.39 to 1.86). Except for coagulation factor VIII and tumor necrosis factor soluble receptor II, these proteins were novel associations and included collagen alpha-3(VI):BPTI/Kunitz inhibitor, histo-blood group ABO system transferase, peroxidasin, human epididymis protein 4, and regulator of G protein signaling 3. KEGG analyses of the top-ranked 200 proteins revealed significant pathway enrichment of nine proteins in the complement (mainly lectin pathway) and coagulation (mainly intrinsic pathway) cascades.Our proteome-wide analysis led to discovery of five novel protein candidates associated with 5-year risk of future VTE. KEGG analyses supported an interplay between the complement and coagulation pathways in the pathogenesis of VTE.
Keywords: proteomics; plasma; aptamer; venous thromboembolism; deep vein thrombosis; pulmonary embolism